Some words about fractures of radial head - SACCOMANNI, BERNARDINO (Jour Med Resh and Health Sci, 2020)
A visible posterior fat pad on the lateral view of the elbow is a sign of occult intraarticular pathology. Early elbow ROM is needed to prevent stiffness. If you fixed the fracture, but not well enough to move the elbow, you did not fix it. The “safe zone” for placing hardware on the radial head lies in the interval between the radial styloid and Lister’s tubercle. Examine the wrist when examining all elbow injuries; a radial head fracture may be accompanied by a tear of the interosseous membrane and disruption of the distal radioulnar joint. The posterior interosseous nerve (controlling finger and wrist extension) can be damaged by a radial head injury or by the surgery performed to treat the fracture. Therefore, document functional status preoperatively. The severity of these injuries runs the gamut from minimally displaced fractures needing minimal treatment to those with major displacement or comminution, requiring surgical fixation, excision, or replacement.